Challenges and Solutions in Coffee Cultivation: A Case Study of Growers in Chikkamagaluru and Kodagu Districts, Karnataka, India - , Bharath H. L.; , Bharath Kumar T. P.; Preethi,; , Sanketh C. V.; , Vinay Kumar R.; , Suresh D, K.; , Basavaraj Beerannavar (Archives of Current Research International, 2025)
Coffee plays a crucial role in various aspects of daily life and industry, offering nutritional and economic benefits to many countries. Consequently, ensuring its production becomes a prime consideration. The current study aims to know the important constraints faced and suggestions by coffee growers at Chikkamagaluru and Kodagu District of Karnataka. These study converse details on extent of adoption practices of coffee growers in above regions. Random sampling method was used to select 120 respondents. The primary data was collected from respondents using pre-tested interview schedule. For this purpose, an ex-post facto research design was employed. The study revealed that, several significant constraints encountered during the adoption of improved cultivation practices in coffee. These included Exploitation by middlemen (I), non-availability of labour (II), high cost of fertilizers and plant protection chemicals (III), fluctuation in market price (IV), problems of pest and diseases (V), indeterminate rainfall (VI), Lack of market information (VII) and High cost of transportation (VIII) were some of the problems faced by the Coffee growers respectively. In response, growers offered valuable suggestions, such as standardized price for the produce (I), eliminating middlemen (II), standardized weighing scales (III), providing access to market information (IV), frame cooperative for collective marketing (V) and the Coffee board should conduct more extensive market research (VI) were the suggestions given by Coffee growers respectively. The findings of this paper explains different challenges faced by the Coffee growers of Chikkamagaluru and Kodagu Districts, Karnataka. If these challenges were solved by the policy makers by making informed decisions to enhance the production and sustainability of coffee farming, then this will contribute to the nation's growth. Coffee plays a crucial role in various aspects of daily life and industry, offering nutritional and economic benefits to many countries. Consequently, ensuring its production becomes a prime consideration. The current study aims to know the important constraints faced and suggestions by coffee growers at Chikkamagaluru and Kodagu District of Karnataka. These study converse details on extent of adoption practices of coffee growers in above regions. Random sampling method was used to select 120 respondents. The primary data was collected from respondents using pre-tested interview schedule. For this purpose, an ex-post facto research design was employed. The study revealed that, several significant constraints encountered during the adoption of improved cultivation practices in coffee. These included Exploitation by middlemen (I), non-availability of labour (II), high cost of fertilizers and plant protection chemicals (III), fluctuation in market price (IV), problems of pest and diseases (V), indeterminate rainfall (VI), Lack of market information (VII) and High cost of transportation (VIII) were some of the problems faced by the Coffee growers respectively. In response, growers offered valuable suggestions, such as standardized price for the produce (I), eliminating middlemen (II), standardized weighing scales (III), providing access to market information (IV), frame cooperative for collective marketing (V) and the Coffee board should conduct more extensive market research (VI) were the suggestions given by Coffee growers respectively. The findings of this paper explains different challenges faced by the Coffee growers of Chikkamagaluru and Kodagu Districts, Karnataka. If these challenges were solved by the policy makers by making informed decisions to enhance the production and sustainability of coffee farming, then this will contribute to the nation's growth.